INVESTIGATION OF SOLAR ABSORPTANCE OF BUILDING EXTERNAL SURFACES FROM HEAT FLUX POINT OF VIEW - Ozel, Meral; Pihtili, Kazim (Pamukkale Univ, 2006)
In this study, solar absorptance of external surfaces of buildings has been numerically investigated from the heat gain and losses point of view. For this purpose, external surface solar absorptance was icreased from 0 to 1with an ratio of 0.1 and, for the summer and winter conditions, heat fluxs was calculated by considering orientations of the wall and its roof for brick and concrete structure materials. Besides, external surface absorptance was assumed as 0.2, 0.5 and 0.9, respectively. Than, heat gain and losses were calculated to insulation thickness increasing on the outdoor surface of wall. Results obtained were presented as graphics
Keywords: Solar absorptance; Orientation of wall; Insulation thickness; Heat gain and loss